Combined NanoSIMS and synchrotron X‐ray fluorescence reveal distinct cellular and subcellular distribution patterns of trace elements in rice tissues. Issue 1 (24th September 2013) - Moore, Katie L.; Chen, Yi; van de, Allison M. L.; Hughes, Louise; Liu, Wenju; Geraki, Tina; Mosselmans, Fred; McGrath, Steve P.; Grovenor, Chris; Zhao, Fang‐Jie
Summary The cellular and subcellular distributions of trace elements can provide important clues to understanding how the elements are transported and stored in plant cells, but mapping their distributions is a challenging task. The distributions of arsenic, iron, zinc, manganese and copper, as well as physiologically related macro‐elements, were mapped in the node, internode and leaf sheath of rice (Oryza sativa) using synchrotron X‐ray fluorescence (S‐XRF) and high‐resolution secondary ion mass spectrometry (NanoSIMS). Although copper and silicon generally showed cell wall localization, arsenic, iron and zinc were strongly localized in the vacuoles of specific cell types. Arsenic was highly localized in the companion cell vacuoles of the phloem in all vascular bundles, showing a strong co‐localization with sulfur, consistent with As(III)–thiol complexation. Within the node, zinc was localized in the vacuoles of the parenchyma cell bridge bordering the enlarged and diffuse vascular bundles, whereas iron and manganese were localized in the fundamental parenchyma cells, with iron being strongly co‐localized with phosphorus in the vacuoles. The highly heterogeneous and contrasting distribution patterns of these elements imply different transport activities and/or storage capacities among different cell types. Sequestration of arsenic in companion cell vacuoles may explain the limited phloem mobility of arsenite.